Anterior-posterior regionalized gene expression in the Ciona notochord - Reeves, Wendy (2013)
BACKGROUND: In the simple ascidian chordate Ciona the signaling pathways and gene regulatory networks giving rise to initial notochord induction are largely understood and the mechanisms of notochord morphogenesis are being systematically elucidated. The notochord has generally been thought of as a non-compartmentalized or regionalized organ that is not finely patterned at the level of gene expression. Quantitative imaging methods have recently shown, however, that notochord cell size, shape and behavior vary consistently along the anterior-posterior (AP) axis. RESULTS: Here we screen candidate genes by whole mount in situ hybridization for potential AP asymmetry. We identify 4 genes that show non-uniform expression in the notochord. Ezrin/radixin/moesin (ERM) is expressed more strongly in the secondary notochord lineage than the primary. CTGF is expressed stochastically in a subset of notochord cells. A novel calmodulin-like gene (BCamL) is expressed more strongly at both the anterior and posterior tips of the notochord. A TGF-β ortholog is expressed in a gradient from posterior to anterior. The asymmetries in ERM, BCamL and TGF-β expression are evident even before the notochord cells have intercalated into a single-file column. CONCLUSIONS: We conclude that the Ciona notochord is not a homogeneous tissue but instead shows distinct patterns of regionalized gene expression.